PENGARUH SUBSTITUSI TEPUNG KEDELAI (Glycine max L.) TERHADAP KARAKTERISTIK ORGANOLEPTIK DAN FISIKOKIMIA CROISSANT - Khairi, Wildan; Nabilah, Nurjihan; Kosmilia, Tri Ana; Wulandari, Dita Albarita; Saputri, Salsabila; Nurtiana, Winda (Leuit (Journal of Local Food Security), 2025)
Croissant is a crescent-shaped bread that is soft inside and crispy outside which has a high market demand. The purpose of this study was to determine the effect of different percentages of soy flour substitution on the acceptability and physicochemical content of croissants. Selected treatments will be further analyzed regarding physical (color and texture) and chemical properties (moisture content, ash content, fat content, protein content, carbohydrate content, and crude fiber). Organoleptic test results showed that sample F4 (80%; 20%) obtained the highest favorability score on the texture parameter. Sample F4 is the selected treatment using the de Garmo method. The results of the physical characterization test include texture (37.26 and 56.46 N) and color in the yellow red color area. While the results of chemical characterization tests include protein content (9.58%); moisture content (0.2151%); ash content (2.1%); fat content (41.98%); carbohydrate content (46.09); crude fiber (5.78%).